VOLCANIC EVENTS RECORD OVER THE LAST 900 YEARS FROM SNOW AND FIRN SEQUENCE IN VOSTOK STATION AREA - T. Hodzher V.; L. Golobokova P.; E. Osipov Yu.; N. Onishchuk A.; U. Filippova G.; V. Lipenkov Yu.; A. Ekaykin A.; Т. Ходжер В.; Л. Голобокова П.; Э. Осипов Ю.; Н. Онищук А.; У. Филиппова Г.; et al. (Ice and Snow, 2015)
The results of chemical analyses of snow samples from five pits and cores drilled in the vicinities of Vostok Station, Antarctica, are presented. High resolution (every 2–3 cm, or about three samples per year) ion measurements allowed to compile a new detailed record of volcanic events for the past 900 years. About 30 low latitude volcanic eruptions were identified In core intervals with high content of nonmarine sulphates and decreased values of acidity during XIII–XX centuries. Global ones analysed in the literature were detected in the cores: Pinatubo (1991), Agung (1963), Krakatau (1883), Tambora (1815), unknown (1809), Gamkonora (1673), Huaynaputina (1600), Kuwae (1453), unknown (1259). Приводятся результаты химического анализа снежно-фирновой толщи района станции Восток по образцам из пяти снежных шурфов и кернов. Детальность отбора проб (каждые 2–3 см) позволила получить хронологию вулканических событий с высокой степенью точности. В интервалах с повышенными концентрациями неморского сульфата и пониженными значениями кислотности идентифицированы сигналы около 30 следов вулканических извержений низкоширотных вулканов на протяжении XIII–XX вв., в том числе глобальных, анализируемых в мировой литературе: Пинатубо (1991 г.), Агунг (1963 г.), Кракатау (1883 г.), Тамбора (1815 г.), неизвестный вулкан (1809 г.), Гамконора (1673 г.), Уайнапутина (1600 г.), Кувае (1453 г.), неизвестный вулкан (1259 г.).